The Influence of Human Resource Competency and Utilization of Information Technology on The Quality of Regional Government Financial Reports With Internal Control As A Moderating Variable (Study On Bekasi City Government) - Nauli, sherly; Daito, Apollo (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study was conducted to test the effect of human resource competence and utilization of information technology on the quality of local government financial reports with internal control as a moderating variable in the Bekasi City Government. The type of data in this study is quantitative data sourced from primary data. The method of data collection by distributing questionnaires. The population in this study was the Regional Finance and Asset Management Agency (BPKAD) of the Bekasi City Government. The sample used in this study were employees in the budget, treasury, accounting and asset fields. Data processing for the study used SmartPLS. The research that has been conducted provides results that human resource competence and utilization of information technology have an effect on the quality of local government financial reports. Furthermore, based on the results of the study, internal control is unable to moderate the relationship between human resource competence and the quality of local government financial reports. Internal control is able to moderate the relationship between the utilization of information technology and the quality of local government financial reports